Beneficial effects of ginger (Zingiber officinale) on carbohydrate metabolism in streptozotocin-induced diabetic rats - Abdulrazaq, Nafiu Bidemi; Cho, Maung Maung; Win, Ni Ni; Zaman, Rahela; Rahman, Mohammad Tariqur (Cambridge University Press, 2011)
Zingiber officinale (ZO), commonly known as ginger, has been traditionally used in the treatment of diabetes mellitus. Several studies have reported the hypoglycaemic properties of ginger in animal models. The present study evaluated the antihyperglycaemic effect of its aqueous extract administered orally (daily) in three different doses (100, 300, 500 mg/kg body weight) for a period of 30 d to streptozotocin (STZ)-induced diabetic rats. A dose-dependent antihyperglycaemic effect revealed a decrease of plasma glucose levels by 38 and 68 % on the 15th and 30th day, respectively, after the rats were given 500 mg/kg. The 500 mg/kg ZO significantly (P < 0·05) decreased kidney weight (% body weight) in ZO-treated diabetic rats v. control rats, although the decrease in liver weight (% body weight) was not statistically significant. Kidney glycogen content increased significantly (P < 0·05) while liver and skeletal muscle glycogen content decreased significantly (P < 0·05) in diabetic controls v. normal controls. ZO (500 mg/kg) also significantly decreased kidney glycogen (P < 0·05) and increased liver and skeletal muscle glycogen in STZ-diabetic rats when compared to diabetic controls. Activities of glucokinase, phosphofructokinase and pyruvate kinase in diabetic controls were decreased by 94, 53 and 61 %, respectively, when compared to normal controls; and ZO significantly increased (P < 0·05) those enzymes' activities in STZ-diabetic rats. Therefore, the present study showed that ginger is a potential phytomedicine for the treatment of diabetes through its effects on the activities of glycolytic enzymes